Extention of Upper Bound Sampling Times for Discrete Implementation of a Continuous Controller - Pudji Astuti (Institute for Research and Community Services (LPPM) ITB, 1998)
Tulisan ini memperbaiki syarat cukup yang diusulkan oleh Astuti dkk sehingga implementasi diskret suatu pengendali kontinu tetap mengendalikan suatu sistem tak linier konvergen ke suatu bola. Seperti juga dalam Astuti dkk, syarat cukup tersebut dapat digunakan untuk menentukan batas atas periode cuplik yang akan menghasilkan sistem kendali data tercuplik yang bersifat konvergen. Lebih dari itu, batas atas yang dihasilkan dapat lebih baik dibandingkan dengan batas atas yang dihasilkan dengan menggunakan syarat cukup di Astuti dkk. Contoh sederhana diberikan untuk mempertunjukkan hasil tersebut. Extention of Upper Bound Sampling Times for Discrete Implementation of a Continuous ControllerThis note improves the sufficient conditions proposed by Astuti et. al. which guarantee the discrete implementation of a continuous controller remains resulting in the convergence of a nonlinear system. As in Astuti et. al. the proposed sufficient conditions can be used to determine an upper bound of sampling times resulting in the convergence of the closed loop sampled data control system. Further, the obtained upper bound of sampling time can be better than the upper bound obtained using the conditions in Astuti et. al. A simple example is given to demonstrate the result.